Penerapan Kegiatan Bermain Fun Cooking Dalam Meningkatkan Tumbuh Kembang Anak Usia 4-5 Tahun - Indi Azma Amania; I Wayan Karta; Ika Rachmayani; I Nyoman Suarta (Indonesian Publication Center, 2021)
Fun Cooking is a cooking activity that is delivered in a fun and simple way depends on the characteristics of early childhood to help their growth and development stimulation process, especially in cognitive aspect that is closely related to reasoning and thinking as well as in socio-emotional aspects related to their behavior and process of adjustment with their environment. As a result, this study was designed at determining the role of fun cooking activities in improving the cognitive and socio-emotional aspects of children. Qualitative Descriptive Method was applied with two children aged 4-5 years with different sexes and coming from Rumak Barat Utara hamlet as the subjects of the data. Furthermore, along the process of data analysis this research used qualitative descriptive analytic in which the data that has been collected will be classified based on their respective groups and analyzed by analytical inductive in order to deduce the conclusions. After the activity is implemented, it is known that Fun Cooking can play a positive role in the cognitive aspects, in classifying, counting, pointing out large and small groups and being able to think about forming dough according to their ideas. On the socio-emotional aspect, it can stimulate cooperation, self-confidence, respecting others, help and sharing in understanding the rules and discipline. Therefore, as the application suggestion, teachers can arrange tools and materials randomly earlier in optimizing the stimulation of children's logical thinking.